Inflammatory Myofibroblastic Tumor of the Urinary Bladder: An 11-Year Retrospective Study From a Single Center - Chen, Can; Huang, Mengjun; He, Haiqing; Wu, Shuiqing; Liu, Mingke; He, Jun; Zang, Hongjing; Xu, Ran (Frontiers in Medicine, 2022)
Purpose To share our experience in the diagnosis and treatment of an inflammatory myofibroblastic tumor of the urinary bladder (IMTUB). Materials and Methods A database searches in the pathology archives by using the term “inflammatory myofibroblastic tumor” and” bladder” in our hospital department of pathology from 2010 to 2021. Patient characteristics, clinical features, histopathological results, immunohistochemical staining results, and treatment outcomes were reviewed. Results Fourteen cases of IMTUB were retrieved. The mean age was 44.7 ± 18.9 years (range 12–74). Nine (64.3%) of the patients presented with hematuria, followed by seven (50%) with odynuria, five (35.7%) with urgent urination, and one (7.1%) with dysuria. Ten (71.4%) of the patients were treated with partial cystectomy (PC), three (21.4%) with transurethral resection of bladder tumor (TURBT), and one (7.1%) with radical cystectomy (RC). Histopathologically, eight (57.1%) had a compact spindle cell pattern. Anaplastic lymphoma kinase (ALK) staining was positive in six (75%) of 8 cases. During a mean follow-up period of 43.9 ± 38 months (range 3–117), a patient had recurrence within half a month. Then, the patient was treated with further TURBT surgery and had no recurrence within 6 months. Thirteen of the patients had no local recurrence or distant metastasis. Conclusion Inflammatory myofibroblastic tumor of the urinary bladder (IMTUB) is clinically rare and has a good prognosis. The disease is mainly treated with surgery to remove the tumor completely. It can easily be misdiagnosed as bladder urothelial carcinoma, leiomyosarcoma, or rhabdomyosarcoma, which may result in overtreatment and poor quality of life of patients.